Yona of the dawn. 30 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2021)
"A red-haired princess loses her family and her kingdom... Now she must rise and fight with her Dragon Warriors by her side! Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! While the Kingdom of Kohka and Sen Province armies battle, Hak goes all out on the front lines and ends up fighting North Kai leader Ying Kuelbo one-on-one! Meanwhile, Yona remains a prisoner in Sen Province and must find a way to overcome Priest Gobi's treachery!"--Amazon.com